Attachment B: statement of work - Instituto Interamericano de Cooperación para la Agricultura (IICA), United States Department of Agriculture (USDA) (USA) (2019)
As a continuation of the 2017 and 2018 activities, this project aims to build capacity of the CACU members to implement food safety and SPS standards or regulations in line with this plan. IICA under this cooperative agreement is partnering with USDA to strengthen the capacity of CACU member nations to achieve the development and adoption on trade-related technical regulations. IICA’s contributions to the project will be conducted in coordination with USDA. The planned duration of the project is from the time of ratification until December 31, 2019.